(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status of patients with chronic obstructive pulmonary disease (COPD) at Bac Ninh No. 2 General Hospital in 2025. Methods: A cross-sectional descriptive study was conducted on 141 patients diagnosed with COPD at Bac Ninh No. 2 General Hospital from May to December 2025. Results: Among the 141 patients, nutritional status was assessed using multiple indicators. According to the Subjective Global Assessment (SGA), 19.1% of patients were classified as severely malnourished, 31.2% were at risk of mild malnutrition, and 49.6% had no nutritional risk. Based on body mass index (BMI), 31.8% were underweight, 61.7% had normal nutritional status, and 6.4% were overweight or obese. Assessment using mid-upper arm circumference (MUAC) showed that 36.2% of patients were malnourished, while 63.8% were not. The prevalence of anemia, based on hemoglobin concentration, was 25.5% (36 patients), with a statistically significant difference between males and females (p < 0.05). According to total lymphocyte count (TLC), 61.7% of patients (87 patients) were classified as malnourished. Conclusion: Malnutrition is a common condition in patients with COPD. Therefore, early nutritional assessment and timely intervention can contribute to improving the treatment prognosis for patients with chronic obstructive pulmonary disease.